Effect of COVID-19 on Dental Education and Practice in France - Gaudin, Alexis; Arbab-Chirani, Reza; Pérez, Fabienne (Frontiers in Dental Medicine, 2020)
The coronavirus disease 2019 (COVID-19) is an acute infectious disease leading to a global pandemic. Dental professionals (dental staff, academics) and students are one part of the healthcare workers that face the greatest severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) risk. Consequently, several measures were imposed to limit the spread of the virus, the overload of the health system, and to protect the dental professionals and students. This brief communication focuses on chronology of COVID-19 related events, the temporary modifications, and the potential impacts on dental education in France.